The paradise. [Season one] [videorecording (DVD)] - Vanderham, Joanna; Elliott, Emun, 1983-; Wight, Stephen, 1980- ([Publisher not identified], 2013)
Set amidst the Victorian splendor of Britain's first department store, The Paradise is a rags-to-riches story of a young girl who falls in love with the intoxicating charms of the modern world. As Denise finds her feet as a lowly shop girl, she must navigate her way through power struggles, intrigues, and affairs. When the shop's dashing and reckless owner, John Moray, spots her talents, she knows she can use this opportunity to rise to great things.